Two Decades of Fiscal Decentralization: Economic Convergence and Regional Disparity. - Sari, Ira Febriana (Eduvest - Journal of Universal Studies, 2025)
Fiscal decentralization in Indonesia has granted substantial authority to regional governments in managing local expenditures, with the expectation of promoting equitable development and economic convergence. However, questions remain regarding the effectiveness of government spending in reducing regional disparities. This study aims to examine the impact of government expenditure and other contributing factors—namely education, fixed capital supply, and the Human Development Index (HDI)—on economic convergence and inequality reduction across Indonesia’s 34 provinces from 2010 to 2019. The research investigates whether these variables contribute to narrowing the development gap using a panel data analysis and the Generalized Method of Moments (GMM) approach. The findings show that government spending positively and significantly supports economic convergence and reduces interregional inequality. However, the effects of education and the Human Development Index are found to be statistically insignificant in reducing disparities. This result may be attributed to persistent inequality in education access and the low educational attainment of much of the Indonesian workforce. These findings suggest that while fiscal policy can drive convergence, complementary policies are required to enhance education quality and accessibility to ensure more inclusive regional development.